Extracellular vesicles in the context of Mycobacterium tuberculosis infection. (May 2021) - Palacios, Ainhoa; Gupta, Shamba; Rodriguez, G. Marcela; Prados-Rosales, Rafael
Highlights: Mycobacterium tuberculosis (Mtb) actively releases extracellular vesicles (EVs) in vitro and in vivo . EV production in mycobacteria is a regulated process. During an ongoing infection, Mtb -produced EVs travel beyond the infected phagocytic cells. Mycobacterial antigen-containing EVs display strong immunomodulatory properties. Mycobacterial EVs are a potential source of infection biomarkers and have vaccinogenic properties. Abstract: The production of extracellular vesicles (EVs) has emerged as an important process in bacterial biology and host-pathogen interactions. Like many other bacteria, mycobacteria, including Mycobacterium tuberculosis ( Mtb ), the causative agent of human tuberculosis (TB), produces EVs in vitro and in vivo . These membrane-enclosed nanoparticles enable Mtb to secrete hydrophobic molecules, proteins, lipids and glycolipids in a concentrated and protected manner and engage in remote interactions with the host. The nature of the material secreted in mycobacterial EVs, the functional attributes of these vesicles and their potential as protective antigens have stimulated great interest in the mycobacterial field. Although the field of EVs in mycobacterial infections is developing, it has already uncovered a whole new dimension for Mtb -host interactions potentially relevant to TB pathogenesis. In this mini-review, we discuss the current evidence supporting an important role of mycobacterial EVs in modulating cellular immune response, the challenges and recent advances in understanding the mechanisms of vesicle biogenesis and the implications for development of new preventive and therapeutic tools against TB.